Chemical characterization of isolated substance of Argemone mexicana L. leaves and cell viability assays and antibacterial activity: in vitro approach - Araujo, Maria Gabriella Silva (2021)
Aim: Isolation and chemical characterization of a substance extracted from leaves of the species Argemone mexicana L. was performed. In addition, the antibacterial activity and cell viability of this substance was determined. Method: The isolation of the substance was performed by classical liquid layer chromatography, for the chemical characterization were made Infrared and Nuclear Magnetic Resonance spectroscopy. Antibacterial activity was determined by the broth microdilution method to determine the minimum inhibitory concentration of the substance. The cell viability assay was performed with the 3- (4,5-dimethyl-2-thiazolyl) -2,5-diphenyl-2Htetrazoliumbromide colorimetric method using J774 macrophage strains. Results: The substance isolated from the species Argemone mexicana L. was identified as berberine alkaloid. The ability to maintain viable cells of the substance was positive, as it not only maintained viable cells but also promoted proliferation of treated macrophages. This alkaloid demonstrated promising antibacterial activity against Gram positive and negative strains, mainly against Pseudomonas aeruginosa at a concentration of 62,5µg/ml. Conclusion: Berberine's ability to maintain and proliferate cells and inhibit bacterial growth suggests its potential for future antimicrobial treatment and in conditions that require stimulation of cell proliferation.